Youth and civic engagement in Southeast Asia: a survey of undergraduates in six countries - Saat, Norshahril; Halimatusa'diyah, Iim; Anamwathana, Panarat; Mohamad Shukri, Syaza Farhana; Gregorio, Veronica L (ISEAS – Yusof Ishak Institute, 2025)
Youths in Southeast Asia have been active in making their voices heard in politics and in society, both online and offline. However, comparative studies on their civic engagement across the region remain wanting.